10.1152/physiolgenomics.00169.2022 (CrossRef Listing of Deleted DOIs, 2000)
The use of virtual reality (VR) in health education is gaining attention; however, evidence regarding its effectiveness in oral health education remains limited. This pilot study involved 13 adolescents (ages 11-14 yr) identified as school-aged English learners and emergent bilingual students enrolled in a nonprofit, community-based after-school academic enrichment program serving racetrack worker families. Participants engaged in two VR animations: one depicting being inside the mouth and fighting bacteria and another on the anatomy of teeth. Additionally, a presentation that emphasized the importance of oral health in overall health was given, along with a demonstration of proper brushing and flossing techniques using dental models. Presurvey results show that this group already has very good oral hygiene habits, with 85% of the respondents reporting that they brushed their teeth twice daily, primarily under the guidance of their parents (84%). After the VR activity, participants rated the experience on a 1-6 Likert scale, with 69% reporting being "highly satisfied" and 31% "satisfied." Similarly, students reported they "learned a lot" (31%), "a moderate amount" (38%), and "quite a bit" (15%), and most of the students rated oral health as "very important" for overall health (69%). These encouraging findings suggest that VR could be used as an engaging tool for oral hygiene education.NEW & NOTEWORTHY Virtual reality (VR) is an emerging tool in health education, though its use in oral health outreach remains limited. This pilot study involved 13 adolescents (average age = 12.3 yr), identified as school-aged English learners and emergent bilingual students, enrolled in a nonprofit community-based after-school program serving racetrack worker families. Participants completed a bilingual (English and Spanish) oral health program using VR, demonstrations, and interactive activities. Findings suggest VR may enhance engagement and oral health learning.